The breeding trend of non-migratory colony of Black-crowned Night Heron at Putrajaya Wetlands - Suhaili, Fakhri Syahmi (2015)
Putrajaya Wetlands which are about 12 years old is believed to be the largest man-made wetlands in this South East Asia and become the habitat of hundreds birds species including migratory birds with mixed-species colony. The mixed-species colony that can be found here are; Purple Heron (Ardea purpurea), Black-crowned Night Heron (Nycticorax nycticorax), Grey Heron (Ardea cinerea), little egret (Egretta garzetta), cattle egret(Bubulcus ibis) and Painted stork (Mycterialeucocephala). A natural establishment of a mixed-species colony in Upper Bisa, Putrajaya Wetland, Presint 16, Putrajaya( 2º 56’04.01’’N and 101º 42’12.33’’E), provide an opportunity for the study of the breeding habitat of Black-crowned night heron. In this study, the number of nest according to the nest development (early nest, nest with eggs, nest with hatching eggs) were recorded in three man-made island, which each island covered with different species of matured trees. The studied were conducted for 12 weeks from 30th May to 28th August 2014, which are beyond their migratory season and it took three hours, once in a week. Binocular and diascope was used in this study. The first island has Ara (Ficus benjamina), a hardwood tree species with a lot of strong brunches producing fruits and grows in an irregular shape from 10 to 25 meter high. The second island has Sea hibiscus (Hibiscus tiliaceus), a small tree species 5-10 meter tall, flowering, with a trunk up to 15cm in diameter and has a curved tree branch. The third island has Tembusu (Fagraea fragrans), a hardwood tree species, 10-20 meter tall, strong branchy and less branched. The average total of nest counted for the first month is 48 nests, second month with 40.67 nests and the last month with 19 nests. From the study, it was observed that the preference habitat of the Black-Crowned Night Heron are Ficus benjamina(50.85%) > Fagraea fragrans(39.24%) > Hibiscus tiliaceus(9.91%) from 1292 total nests record for 3 month period. This studied showed that, Black-Crowned Night Heron can breed beyond their migratory and breeding season. This is because of the environment in this artificial wetland were conducive, also provide enough source of food and proved that Black-Crowned Night Heron become the residence of this wetland. This study is important for the future conservation of the mixed-species colony waterbird.